IMPLEMENTATION OF ARTICLE 88 REGULATION OF THE MINISTER OF HOME AFFAIRS NUMBER 120 OF 2018 CONCERNING AMENDMENT TO REGULATION OF THE MINISTER OF HOME AFFAIRS NUMBER 80 OF 2015 CONCERNING ESTABLISHMENT OF LOCAL LEGAL PRODUCTS - Anna Ekawati Adam; Lintje Anna Marpaung (PRANATA HUKUM, 2023)
Based on the provisions of Article 88 paragraph (2) Permendagri 120/2018 jo. Permendagri 80/2015 Raperda after discussion must be facilitated. Facilitation is an act of coaching carried out by the Minister of Home Affairs to the Regional Government. Facilitation is carried out to minimize the cancellation of regional regulations. How is the implementation and the inhibiting factors for the implementation of Article 88 paragraph (2) Permendagri 120/2018 jo. Permendagri 80/2015. Inhibiting factors: lack of socialization related to the mechanism for facilitating draft local regulations, limited number of drafting staff of laws and regulations, discrepancy between the number of regional legal product drafts with the time limit set by law, and the low quality of the proposed draft regional regulations for facilitation. Thus, it is necessary to pay attention to the facilitation mechanism in the formation of legal products and add qualified drafters of statutory regulations.